Block Coding in Elementary Mathematics Education: A Systematic Literature Review - I Wayan Suantara; I Putu Andika Subagya Putra; I Nyoman Triesaputra; Alexander Hamonangan Simaniora (MIMBAR PGSD Undiksha, 2025)
The integration of digital technologies in education has transformed the teaching of foundational subjects like mathematics, especially at the elementary level. However, a gap remains between the demands of 21st-century learning and conventional instructional practices. This study aims to analyze the use of block-based coding tools in elementary mathematics education through a Systematic Literature Review (SLR), following the PRISMA 2020 guidelines. A total of 230 articles were initially retrieved from Google Scholar, Scopus, ERIC, and ScienceDirect. After applying inclusion criteria, 12 eligible studies were thematically analyzed using a structured data extraction and synthesis protocol. Findings indicate that block-based coding, particularly via Scratch, significantly enhances students’ conceptual understanding, problem-solving skills, spatial reasoning, and computational thinking. Interactive visual programming environments were also found to boost student motivation and engagement. However, the success of implementation is closely tied to teacher preparedness, technological support, and appropriate curriculum integration. This review concludes that block coding holds strong potential as a transformative pedagogical approach in mathematics education. The findings imply that ongoing teacher professional development and structured curriculum design are essential to ensure effective and scalable integration of coding into elementary mathematics instruction.